Firm Value in the ESG Era: The Role of Corporate Social Responsibility, Good Corporate Governance, and Financial Performance in Indonesian LQ45 Companies - Ningrum, Syifaaa; A Zuliansyah; Arifa Kurniawan (Institut Agama Islam Negeri Kendari, 2026)
Firm value is a key indicator used by investors to assess corporate performance and future prospects. This study aims to examine the effects of Corporate Social Responsibility (CSR), independent commissioners, institutional ownership, and financial performance on firm value in LQ45 companies listed on the Indonesia Stock Exchange during 2021–2024. This research employed a quantitative causal-comparative design using secondary data. The population consisted of 45 LQ45 companies, and 24 companies were selected through purposive sampling, resulting in 96 observations. Data were analyzed using panel data regression with the Fixed Effect Model. The results indicate that CSR, independent commissioners, and institutional ownership do not significantly affect firm value, while financial performance has a positive and significant effect. Simultaneously, all independent variables influence firm value. These findings highlight the importance of profitability in enhancing firm value.